Patellar tracking in primary total knee arthroplasty. Issue 4 (27th April 2018) - Donell, Simon
Abstract : This is a review of the recent literature of the various factors that affect patellar tracking following total knee arthroplasty (TKA). Patellar tracking principally depends on the pre-existing patellar tracking and the rotational alignment of the femoral and tibial implants, but the detailed movements depend on the patellar shape. The latter means that the patellar kinematics of any implanted TKA does not return to normal. Laboratory cadaveric studies use normal knees and non-activity-based testing conditions and so may not translate into clinical findings. The recent literature has not added anything significant to change established clinical practice in achieving satisfactory patellar tracking following TKA. Cite this article: EFORT Open Rev 2018;3:106-113. DOI: 10.1302/2058-5241.3.170036.